1999
DOI: 10.1002/(sici)1097-0010(199901)79:1<137::aid-jsfa210>3.3.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Determination of nitrogen and ash contents in total herbage and botanical components of grassland systems with near infra‐red spectroscopy

Abstract: : Near infra-red reýectance spectroscopy (NIRS) was used to develop calibration equations to measure nitrogen and ash contents in grassland samples. Four populations of samples were collected or prepared : total herbage, with a heterogeneous and complex botanical composition, and its botanical components (grasses, legumes and forbs). A set of samples from each population was selected to develop the speciüc calibration equations using three mathematical data treatments (log 1/R, ürst and second derivative). Six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…In our study, R 2 CV ranged from 0.77 to 0.94 and SEP ranged from 4.9 to 20.0 g/kg DM. Ruano-Ramos et al (1999) report results similar to those found for lucerne, red clover, timothy and permanent grasslands, whereas the SEP obtained by Windham et al (1991) came closest to the SEP obtained for Italian rye-grass samples. These authors highlight the importance of soil contamination in the SEP obtained, particularly when equations were generated with first or second derivatives of log 1/R.…”
Section: Nir Spectral Regionssupporting
confidence: 75%
See 2 more Smart Citations
“…In our study, R 2 CV ranged from 0.77 to 0.94 and SEP ranged from 4.9 to 20.0 g/kg DM. Ruano-Ramos et al (1999) report results similar to those found for lucerne, red clover, timothy and permanent grasslands, whereas the SEP obtained by Windham et al (1991) came closest to the SEP obtained for Italian rye-grass samples. These authors highlight the importance of soil contamination in the SEP obtained, particularly when equations were generated with first or second derivatives of log 1/R.…”
Section: Nir Spectral Regionssupporting
confidence: 75%
“…In theory, inorganic substances do not have near-infrared absorption bands. However, successful CA measurements by NIRS have been reported for grasses and lucerne by Clark et al (1987) and for pastures by Windham et al (1991) and Ruano-Ramos et al (1999). The perfect correlation between CA and organic matter content could explain these good results.…”
Section: Nir Spectral Regionsmentioning
confidence: 98%
See 1 more Smart Citation
“…Near-infrared spectroscopy is based on diffuse reflectance of dried and ground samples and this technique is widely used for constituent assessment of crops in the laboratory (e.g. Berardo, 1997;Ruano-Ramos et al, 1999). Some successful efforts have been made to relate diffuse reflectance of undried material to constituent composition (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to other research results from semi-natural grassland biomass [9,10,18,19], the mineral concentration values for the L0 biomass are within the expected range for biomass harvested in June; however, the values for the L100 samples for Ca, Mg and N were considerably higher. This corresponds with previous findings, which likewise found higher mineral content, particularly for Ca, Mg and N [20,21], in legumes and other dicotyledonous plants compared to grasses. However, the observed values for mineral composition, especially for N, K, Mg, S and Cl, led to the conclusion that a direct combustion of the material, be it lupine, semi-natural grassland biomass, or any mixture of the two, as press fluid and press cake originating from grassland biomass with lupine content between 0 (L0) and 100% FM (L100).…”
Section: Chemical Composition Of Silage and Press Cakementioning
confidence: 99%